Global gyrokinetic simulations of ITG turbulence in the magnetic configuration space of the Wendelstein 7-X stellarator. (18th August 2020) - Bañón Navarro, A; Merlo, G; Plunk, G G; Xanthopoulos, P; von Stechow, A; Di Siena, A; Maurer, M; Hindenlang, F; Wilms, F; Jenko, F
Abstract: We study the effect of turbulent transport in different magnetic configurations of the Weldenstein 7-X stellarator. In particular, we performed direct numerical simulations with the global gyrokinetic code GENE-3D, modeling the behavior of Ion Temperature Gradient turbulence in the Standard, High-Mirror and Low-Mirror configurations of W7-X. We found that the Low-Mirror configuration produces more transport than both the High-Mirror and the Standard configurations. By comparison with radially local simulations, we have demonstrated the importance of performing global non-linear simulations to predict the turbulent fluxes quantitatively.